2002
DOI: 10.1034/j.1600-0412.2002.811112.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐analyzes based on a prospective, randomized study comparing laparoscopic colposuspension with a tension‐free vaginal tape procedure

Abstract: Cost-analyzes based on a prospective, randomized study comparing laparoscopic colposuspension with a tension-free vaginal tape procedure.Persson, Jan; Teleman, Pia; Etén-Bergquist, Christina; Wölner-Hanssen, PålPublished in: Acta Obstetricia et Gynecologica Scandinavica DOI: 10.1034/j. 1600 -0412.2002 .811112.x Published: 2002 Link to publication Citation for published version (APA): Persson, J., Teleman, P., Etén-Bergquist, C., & Wölner-Hanssen, P. (2002). Cost-analyzes based on a prospective, randomized st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 24 publications
1
57
0
3
Order By: Relevance
“…Ultimately, the deciding factor may be cost. One cost-analysis study comparing the two procedures suggested that overall costs are lower with the laparoscopic Burch procedure [55].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the deciding factor may be cost. One cost-analysis study comparing the two procedures suggested that overall costs are lower with the laparoscopic Burch procedure [55].…”
Section: Discussionmentioning
confidence: 99%
“…From these studies, it is apparent that TVT has a much better costbenefit ratio than the Burch colposuspension. However, a laparoscopic Burch colposuspension was slightly cheaper in one study, which may be due to the health financing system in Sweden [62]. In a Dutch study comparing all costs of several treatments for SUI, it was shown that the least expensive treatment was physiotherapy, followed by TVT [63].…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…In addition, for the last two studies [18,19] a urethral functional length of 25 mm or more was required. The exclusion criteria were symptomatic urge incontinence, urodynamicaly demonstrable detrusor instability, previous incontinence or prolapse surgery or a vaginal descent more than grade one cystocele according to Beecham's classification [20] The preoperative investigation was performed by a restricted number of physicians (n=4) and included demographic and contraceptive history, urodynamics, gynaecological investigation, measurement of residual urine, cystoscopy and a standardized short term pad-test [21].…”
Section: Methodsmentioning
confidence: 99%
“…3: a prospective randomized study comparing costs between laparoscopic colposuspension and the TVT procedure [17][18][19], the latter being a part of a larger currently ongoing study (study nr 4) comparing clinical outcome for these two procedures.…”
Section: Methodsmentioning
confidence: 99%